A novel compound heterozygous variation in the FKBP10 gene causes Bruck syndrome without congenital contractures: A case report - Shang, Liyuan; Shi, Weizhe; Xu, Yibo; Nong, Tianying; Li, Xia; Li, Zhaohui; Liu, Yanhan; Li, Jingchun; Tang, Ya-Ping; Zhu, Mingwei; Xu, Hongwen (Heliyon, 2024)
Bruck syndrome (BS) is an extremely rare autosomal-recessive connective tissue disorder mainly characterized by bone fragility, congenital joint contracture, and spinal deformity. It is also considered as a rare form of osteogenesis imperfecta (OI) due to features of osteopenia and fragility fractures. Its two forms, BS1 and BS2, are caused by pathogenic variations in FKBP10 and PLOD2, respectively. We aimed to improve the clinical understanding of BS by presenting a case from China and to identify the genetic variants that led to this case. OI was suspected in a Chinese boy with a history of recurrent long bone fractures, lumbar kyphosis, and dentinogenesis imperfecta (DI). Whole-exome sequencing (WES) was performed to identify pathogenic variations. Sanger sequencing was used to confirm the results of the WES. In silico analysis was used to predict the pathogenicity of genetic variants. WES and Sanger sequencing revealed a compound heterozygous variation in the FKBP10 gene (NM_021939, c.23dupG in exon 1, and c.825dupC in exon 5). Both variants resulted in a frameshift and premature stop codon. Of these two variants, c.23dupG has not been previously reported. The patient's parents were heterozygous carriers of one variant. In addition, zoledronic acid treatment improved the vertebral deformity and bone mineral density (BMD) significantly in this patient. A novel compound heterozygous variation of FKBP10, c.23dupG/c.825dupC, was identified in a patient with moderately severe OI. Based on these findings, the patient was diagnosed with BS1 without congenital joint contractures or OI type XI. This study expands the spectrum of FKBP10 genetic variants that cause BS and OI.